Epidemiological, clinical and ophthalmologic characteristics of patients with keratoconjunctivitis Sicca - Marisela Smith Diburnet; Ana Celia Pérez Ruíz; Elens Galán Ávila; Danay Duperet Carvajal; Yaimet Pérez Infante (Centro Provincial de Información de Ciencias Médicas, 2021)
Introduction: The keratoconjunctivitis sicca is a disease of multifactorial cause that affects the production of tears and the ocular surface, at the same time that causes discomfort, blurred vision and instability of the lacrimal thin layer.  Methods: A descriptive and cross-sectional study of 50 patients with diagnosis of keratoconjunctivitis sicca, assisted in the Ophthalmolgic Center of Dr. Juan Bruno Zayas Alfonso Teaching General Hospital in Santiago de Cuba, was carried out  from January to July, 2020.   Objective: To characterize patients with keratoconjunctivitis sicca according to clinical, epidemiologic and ophthalmologic variables.  Results: In the series there was a prevalence of the females (66.0 %), patients over 60 years (40.0 %),  excessive reading as risk factor (42.0 %),  irritation, ocular fatigue and  blurred vision as diagnostic criteria, besides the decrease of the lacrimal thin layer break up time in 68.0 % of the sample, among other results.   Conclusion: The keratoconjunctivitis sicca was similar to that described in the specialized literature review as for the age groups, sex and main described symptoms from the clinical and epidemiologic points of view.